Hubungan Konsumsi Makanan Jajanan dengan Kejadian Diare pada Siswa di Sekolah Dasar Negeri 008 Batam Kota Kelurahan Baloi Permai Tahun 2024 - Nur Hafizah Putri; Ditte Ayu Suntara (PPNI UNIMMAN, 2025)
Diarrhea is the third leading cause of death in children. WHO estimates that the prevalence of diarrhea globally is almost 1.7 billion cases of diarrhea in children each year, in Indonesia the prevalence of diarrhea is 4.55% of cases. The incidence of diarrhea is caused by several factors, one of which is consuming street food. This study aims to determine the relationship between snack consumption and the incidence of diarrhea in students at Elementary School 008 Batam City, Baloi Permai Village in 2024. The design of this study used cross-sectional. This study was conducted on students in grades IV, V, and VI totaling 50 students. The sampling technique used non-probability sampling with purposive sampling technique. The measuring instrument in this study was a questionnaire on snack food consumption and diarrhea incidence. The results of the study showed that the incidence of diarrhea in students with the category of always consuming snack foods was 4 students (33.3%), often consuming snack foods was 14 students (87.5%), sometimes consuming snack foods was 7 students (53.8%), and never consuming snack foods was 3 students (33.3%). Based on the results of the Chi-Square Test statistic using SPSS, the probability value (p) was smaller than alpha (0.013)